Consequences of the COVID-19 Pandemic on Mental Health: A Review Study - Darbani, Shoaleh; Mirzaei, Abasat (Journal of Assessment and Research in Applied Counseling (JARAC), 2022)
Background and Aim: Coronavirus was first diagnosed in Wuhan, China. The occurrence of this pandemic and the measures taken to control and stop the chain of its transmission sometimes lead to numerous psychological problems that leave long-term effects, and its consequences continue. The outbreak of infectious diseases affects mental disorders in several ways. It can affect pre-existing mental diseases, cause new psychological symptoms in people due to the mutual effects of immunity and mental illness, cause suffering in the guardians of the patients, and lead to stigma. Methods: The present review research examined studies on the consequences and psychological interventions during the coronavirus pneumonia from March 2019 to September 2020 using the keywords, coronavirus, pneumonia, psychological interventions in crises, mental health, COVID-19, pandemic, by searching reliable websites, namely PubMed, Science Direct, Scopus, Google Scholar, ProQuest, and domestic databases such as ACECR, IranMedex, and Magiran. Furthermore, it examined articles published online by the National Health Commission of China, the National Center for Disease Prevention and Control, and the World Health Organization (WHO). Results: The review of 48 final articles indicated that negative psychological effects such as post-traumatic stress disorder, depression, anxiety, stress, sleep disorders, and anger increased significantly in the treatment staff and those with COVID-19 during its pandemic. The review of reliable sources also indicated that the psychological consequences of COVID-19 were different in medical and healthcare personnel, the public, infected patients, patients' families, and children. Conclusion: The perspective of health psychology provided care strategies for different people and for reducing the effects of quarantine. According to the literature review, the individuals' mental health, especially the mental health of medical workers involved in this disease, decrease during the COVID-19 pandemic; hence, it is necessary to provide quick, continuous, and timely psychological interventions